Revisión de la diversificación de la matriz energética para la obtención de energía eléctrica mediante FNCE en Colombia (2023)
The objective of this research is to analyze the technical feasibility of implementing non-conventional energy sources to achieve an expansion of the Colombian energy matrix. The study is carried out based on the identification of different environmental phenomena and constant changes in the climate that affect the current energy matrix, also evidencing examples that help address the need to have energy production with several aspects and not depend largely on hydroelectric energy as is currently the case in the Colombian country, the above by using a qualitative methodology, by searching and collecting different articles and publications that justify what is written in this text. As the main results of the work, it was found that both social and environmental impacts as well as natural phenomena make depending on hydroelectric energy as a generation of electrical energy not the most convenient and creates the need to expand the Colombian energy matrix. It can also be seen in the study that, just as the use of non-conventional energy sources is promoted, it is not viable to make an energy transition without taking into account fossil fuels since at this time the majority of energy production is done through oil, coal and gas extraction.